Interaction of a gold(i) dicarbene anticancer drug with human telomeric DNA G-quadruplex: solution and computationally aided X-ray diffraction analysis. Issue 45 (31st October 2018) - Guarra, Federica; Marzo, Tiziano; Ferraroni, Marta; Papi, Francesco; Bazzicalupi, Carla; Gratteri, Paola; Pescitelli, Gennaro; Messori, Luigi; Biver, Tarita; Gabbiani, Chiara
Abstract : Solution and solid-state data give a quite clear picture for a bis carbene gold(i ) complex having perspective anticancer properties. Abstract : The bis carbene gold(i ) complex [Au(1-butyl-3-methyl-2-ylidene)2 ]PF6, ([Au(NHC)2 ]PF6 hereafter), holds remarkable interest as a perspective anticancer agent. The compound is stable under physiological like conditions: its original structure is retained even in the presence of excess glutathione (GSH). Previous studies revealed its high cytotoxicity in vitro that correlates with the impairment of crucial metabolic and enzymatic cellular processes (Magherini et al., Oncotarget, 2018, 9, 28042). Here, the interaction of [Au(NHC)2 ]PF6 with the human telomeric DNA G-quadruplex Tel23 has been investigated in solution by means of high resolution mass spectrometry. ESI MS experiments well document the formation of stable 1 : 1 adducts between the biscarbene gold complex – in its intact form – and the DNA G-quadruplex Tel23. Next, through independent biophysical methods, we show that [Au(NHC)2 ]PF6 binding does not significantly affect the G quadruplex melting temperature nor its conformation. The crystal structure for the [Au(NHC)2 ] + /Tel24 adduct was eventually determined by a joint X-ray diffraction and in silico simulation approach. Through the careful integration of solution and solid-state data, a quite clear picture emerges for the interaction of this gold complex with the Tel23 G-quadruplex.